Anemia berhubungan dengan Perdarahan Post Partum - Yasin, Zakiyah; Hannan, Mujib; Wahyuni, Erlyn (Fakultas Ilmu Kesehatan, 2021)
Pregnant women who experience anemia and untreated until the end of pregnancy will have an effect at the time of delivery, so that it can cause post partum hemorrhage which results in death in the mother. This study aims to analyze the relationship between anemia and the incidence of post partum hemorrhage in Puskesmas Lenteng, Lenteng District, Sumenep Regency. The study design was analytic with a retrospective approach, the total population was 35 mothers, the total sample was 29 mothers, the sampling technique used random sampling. The independent variable is anemia, the dependent variable is the incidence of post partum hemorrhage. Collecting data using a checklist, data analysis using the chi square statistical test, the value of a = 0.05. The results showed that of the 29 women who gave birth, most of them experienced anemia (HB level <11 g%) during pregnancy, as many as 19 mothers gave birth (65.5%), and of the 29 mothers gave birth, most of them experienced post partum hemorrhage as much as 17 mothers gave birth (59%). The result of statistical tests using chi square with a value of a = 0.05, the resulting value (ρ) = 0.000, so that the value (ρ) <a (0.000 <0.05), which means that H0 is rejected and H1 is accepted, i.e. the relationship between anemia and the incidence of post partum hemorrhage at the Lenteng Public Health Center, Lenteng District, Sumenep Regency in 2020 In order to reduce the incidence of post partum hemorrhage, it is hoped that the mother in labor can prevent anemia during pregnancy, namely by consuming foods that contain lots of protein such as meat, liver, eggs, vegetables, folic acid (Vitamin C) and consumption of Fe tablets regularly and how to drink properly and according to conditions / needs.